Perbandingan Kadar Perbandingan Kadar Fenolik Ekstrak Daun Karet Kebo (Ficus elastica) Hasil Ekstraksi Bertingkat Menggunakan Metode Spektrofotometri UV-Vis - mondo, zhafira anggraini; Suhaenah, Asriani; Tahir, Masdiana (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
ZHAFIRA ANGGRAINI MONDO. Comparison of Phenolic Content of Rubber Kebo (Ficus elastica) Leaf Extract Results from Multilevel Extraction Using the UV-Vis Spectrophotometry Method (Supervised by Asriani Suhaenah and Masdiana Tahir). The kebo rubber plant (Ficus elastica) is used by Indonesian people as traditional medicine, namely medicine to lower blood pressure, lower cholesterol, stroke, and reduce joint pain. Kebo rubber leaves (Ficus elastica) contain secondary metabolites such as saponins, polyphenols, flavonoids and tannins. This research aims to determine the comparison of phenolic compound levels of kebo rubber leaf extract (Ficus elastica) resulting from multilevel extraction using the UV-vis spectrophotometric method. The extraction process uses 3 different types of solvents, namely n-hexane (nonpolar), ethyl acetate (semipolar) and ethanol (polar) using a sonicator. Determination of phenolic content using the UV-Vis spectrophotometric method, with a maximum wavelength of 772 nm and using gallic acid as a comparison. The results showed that the levels were influenced by the solvent used in comparing the phenolic compound levels of kebo rubber leaf extract (Ficus elastica) with the multilevel extraction method, namely n-hexane extract 3,774 mgGAE/g, ethyl acetate extract 12,696 mgGAE/g, ethanol extract 74,396 mgGAE/g g.